2021
DOI: 10.1038/s41586-021-03693-y
|View full text |Cite
|
Sign up to set email alerts
|

BNT162b2-elicited neutralization of B.1.617 and other SARS-CoV-2 variants

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
243
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(280 citation statements)
references
References 29 publications
36
243
1
Order By: Relevance
“…A recent multicenter prospective cohort study in England found vaccine effectiveness upwards of 85% (19). Our results support high levels of protection afforded by vaccination, particularly among recipients of both doses (9,15,(20)(21)(22)(23)(24). The majority of cases in our study were among partially vaccinated individuals, emphasizing the importance of personal protective measures, and susceptibility to infection particularly until fully vaccinated (19,(24)(25)(26)(27).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…A recent multicenter prospective cohort study in England found vaccine effectiveness upwards of 85% (19). Our results support high levels of protection afforded by vaccination, particularly among recipients of both doses (9,15,(20)(21)(22)(23)(24). The majority of cases in our study were among partially vaccinated individuals, emphasizing the importance of personal protective measures, and susceptibility to infection particularly until fully vaccinated (19,(24)(25)(26)(27).…”
supporting
confidence: 76%
“…The reports of mutants, known as Variants of Concerns (VOCs) that exhibit increased transmission or immune evasion, or both, have been reported in different global regions and predominant lineages have been genotyped (5). Of note, three VOCs, B.1.1.7 (recently named Alpha) (6), B.1.351 (Beta) (7), and P.1 (Gamma) (8) containing prominent mutations in the spike protein, emerged in the UK, South Africa and Brazil, respectively, and more recently, B.1.617.2 (Delta) (9) emerged in India and has spread globally. The mapping of specific mutations in the spike protein has revealed strong evidence of convergent evolution, and particularly the E484K polymorphism, which is able to evade certain monoclonal therapy and it is less responsive to neutralizing antibodies from recovered patients.…”
Section: Introductionmentioning
confidence: 99%
“…The increased transmissibility and/or pathogenicity of the variants is due, at least in part, to mutations in the spike protein RBD that increase its affinity for ACE2 on target cells. Mutations in the Beta, Gamma and Delta variant spike RBDs have been shown to cause partial resistance to neutralization by the serum antibodies of vaccinated and convalescent individuals and therapeutic monoclonal antibodies [4][5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about its sensitivity to the humoral immune response. Recent reports indicated a reduced sensitivity of members of the B.1.617 lineage to certain monoclonal and polyclonal antibodies [1][2][3][4][5][7][8][9] .…”
mentioning
confidence: 99%